Effect of Nickel Content on the Corrosion Resistance of Iron-Nickel Alloys in Concentrated Hydrochloric Acid Pickling Solutions - Nabeel Alharthi; El-Sayed M. Sherif; Hany S. Abdo; S. Zein El Abedin (Advances in Materials Science and Engineering)
The effect of Ni content on the resistance against corrosion of Fe-36% Ni and Fe-45% Ni alloys in 1 M hydrochloric acid pickling solution was reported. Various electrochemical and spectroscopic techniques such as potentiodynamic cyclic polarization (CPP), open-circuit potential (OCP), electrochemical impedance spectroscopy (EIS), potentiostatic current-time (PCT), and scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) have been employed. CPP measurements indicated that the corrosion current and corrosion rate recorded lower values for the alloy that had higher nickel content. OCP curves proved that the presence of high Ni content shifts the absolute potential to the positive potential direction. EIS results revealed that the surface and polarization resistances were much higher for the alloy with higher Ni content. PCT curves also showed that the absolute currents were lower for Fe-45% Ni alloy. All results were in good agreement with others and confirmed clearly that the corrosion resistance in HCl solutions for Fe-45% Ni alloy was higher than that obtained for Fe-45% Ni alloy.